Appraisal Of Sediment Transport Equations - Cheng, Kok Leong (Universiti Sains Malaysia, 2006)
For history, we know that river is a foundation in building and expanding a civilization. River is not just a source for water, food and transportation but also contributing many other advantages to human activities such as agricultural, industrial, electricity power and other. However, it also can cause massive destruction during floods. This happens when equilibrium becomes unstable with human activities. So, human should think of ways and means to save the river from pollution, erosion and sedimentation. In order to control and prevent erosion and sedimentation, studies should be carried out on sediment transport in rivers. By these ways of control and prevention, flood disasters will be under control and should not occur in the future. Therefore, this study is carried out on Kulim River in Kedah. This study also involves in collecting raw data which concerns about erosion and sedimentation like bed load, suspended load and bed material. Measurements carried out include the geometry data of depth, river cross section, slope, sediment size, viscosity and water discharge are collected too. These data are used for further calculation and evaluvation with bed load transport equations and total bed material load transport equations. The results show that Eugelund – Hansen and Graf equation are able to predict satisfactorily the measured load.